Soil irrigation effect of sugar mill effluent on changes of growth and biochemical contents of Raphanus sativus L. - Sureshkumar1, A. Natarajan2, P. Vijayarengan2, S. Sharavanan2, M. Vijayaragavan1*, C. Prabhahar3, J. (Current Botany, 2011)
The effect of sugar mill effluent on plant growth and biochemical constituents of Raphanus sativus L. var. Pusha Chetki was studied in a pot culture experiment. The experiment was conducted at Botanical Garden, Department of Botany, Annamalai University, Tamil Nadu, during the period of January to March 2008. In the pot culture experiment, radish plants were grown up to 60Ã‚Â days, in the soil irrigated with different concentrations of sugar mill effluent (viz, 0, 20%, 40%, 60%, 80% & 100%v/v). The inner surface of pots was lined with a polythene sheet. Each pot containing 5kg of air dried soil. Six seeds were sown in each pot. All pots were irrigated (500ml) with respective concentration of test solutions daily. Plants were thinned to a maximum of three per pots, after a week of germination. The higher sugar mill effluent concentrations (above 40%) were found to affect plant growth and decreased chlorophyll-a, chlorophyll-b and total chlorophyll, caroteinoids, total sugar, amino acids and protein contents, but diluted effluent (up to 40% ) favoured the plant growth and biochemical contents.